DYNAMICS OF MINING CONFLICT IN KONAWE ISLANDS: RELIGIOUS MODERATION MOVEMENT IN NEGOTIATION OF CONFLICT - Giling, Mustamin; Ulama’i, Khaerul Asy’ary; Ibnu Azka; Rachmat Adiwijaya; Fathur Baldan Haramain (Khazanah: Jurnal Studi Islam dan Humaniora, 2024)
This study explores the dynamics of mining conflicts in the Konawe Islands, with a focus on the role of the religious moderation movement in negotiating and resolving these conflicts. Mining activities in the region, particularly on Wawonii Island, have triggered significant social, environmental, and economic issues, leading to conflicts between the local community, mining companies, and government institutions. The aim of this study is to examine how religious moderation, defined as efforts to promote balance, tolerance, and peaceful coexistence among different religious groups, can be applied as a conflict resolution strategy in mining disputes. This research is qualitative, with data collected through participant observation, interviews, and documentation. Data analysis involves coding, categorization, and interpretation to understand the conflict and the conflict negotiation process. The findings of this study show that religious moderation has the potential to bridge the gap between opposing groups by fostering mutual understanding and tolerance. Religious leaders play an important role in disseminating peace and facilitating communication between conflicting parties. However, challenges such as economic interests and deeply rooted views on mining activities hinder the full effectiveness of religious moderation in resolving this conflict. This study contributes to the broader discourse on the role of religion in conflict resolution, particularly in regions experiencing resource extraction conflicts. It also highlights the need for more collaborative efforts from local governments, religious institutions, and civil society to ensure sustainable conflict resolution in mining-affected areas